S. epidermidis : how to turn from commensal to be a pathogen lifestyle - Titik Nuryastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Staphylococcus epidermidis normally is a commensal inhabitant of healthy human skin and mucosa, but also a common nosocomial pathogen in immunocompromised patients, neonates, and patients with indwelling medical devices. To distinguish the pathogen and commensal strain is a big challenge when identifying this agent with its related infection. This mini-review aims to summarize recent research in this area with a special emphasis on the virulence factor of generating genotypic and phenotypic diversity in S. epidermidis.By living between a commensal and pathogen, S. epidermidis needed to establish many strategies to face different clinical environments, including the new ecological niche of biomaterials. In addition, the growing number of immunocompromised patients increased the risk for a very sensitive host. However, further exploration of the relationship between virulence factor and in vivo pathogenesis is still needed. According to the virulence factor of these bacteria, which are considered as a real pathogen, strict control measures should be taken for S. epidermidis infection.